COVID-19 associated Kawasaki-like multisystem inflammatory disease in an adult - Sokolovsky, Sabrina (Am J Emerg Med, 2021)
Recent reports have described a secondary Multisystem Inflammatory Syndrome in Children (MIS-C) after a prior COVID-19 infection that often has features of Kawasaki disease (KD). Here, we report the case of a 36-year-old woman who presented to the emergency department hypotensive and tachycardic after 1 week of fevers, abdominal pain, vomiting and diarrhea, and was found to have the classic phenotype of complete Kawasaki's Disease including nonexudative conjunctivitis, cracked lips, edema of the hands and feet, palmar erythema, a diffuse maculopapular rash, and cervical lymphadenopathy. Initial laboratory studies were significant for hyponatremia, elevated liver function tests including direct hyperbilirubinemia, and leukocytosis with neutrophilia. Imaging revealed mild gallbladder wall edema, a small area of colitis, and small pleural effusion. She was treated for Kawasaki Disease Shock Syndrome (KDSS) with pulse dose solumedrol, IVIG, and aspirin with near resolution of symptoms and normalization of vital signs within 1 day and subsequent improvement in her laboratory abnormalities. She was later found to be COVID-19 IgG positive, suggesting past exposure. This case represents an early report of a KD-like illness in an adult with serologic evidence of a previous COVID-19 infection, similar to MIS-C. It suggests that the virulent strain of SARS-CoV-2 appears to cause a post-infectious inflammatory syndrome similar to KD in adults, as well as children. Our understanding of the myriad of COVID-19 symptoms and sequelae is rapidly evolving. We recommend physicians remain vigilant for inflammatory syndromes that mimic KD/KDSS which may warrant prompt treatment with IVIG and steroids.